2014
DOI: 10.1007/s13277-014-2472-1
|View full text |Cite
|
Sign up to set email alerts
|

TES was epigenetically silenced and suppressed the epithelial–mesenchymal transition in breast cancer

Abstract: The TES gene was frequently lost in breast cancer, which could inhibit tumor invasion and the formation of distant metastasis. However, the underlying mechanisms remain unknown yet. In the present study, we aimed to investigate how TES was silenced and its roles in EMT--the key step for tumor metastasis. Real-time polymerase chain reaction (PCR) and Western blot were used to detect the mRNA and protein expression of target genes; the status of TES promoter was determined by methylation-specific PCR and subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This gene is involved in tumor cell growth and metastasis [ 91 ]. In this patient’s VPGL, we also observed a variant NM_015641: c.G1123A, p.V375M (chr7: 115897393, rs202205760) in TES , a tumor suppressor gene involved in the regulation of tumorigenesis, angiogenesis, and metastasis [ 92 ]. Additionally, a likely pathogenic variant NM_017672: c.C1337G, p.A446G (chr15: 50916466) in the TRPM7 gene was found.…”
Section: Resultsmentioning
confidence: 99%
“…This gene is involved in tumor cell growth and metastasis [ 91 ]. In this patient’s VPGL, we also observed a variant NM_015641: c.G1123A, p.V375M (chr7: 115897393, rs202205760) in TES , a tumor suppressor gene involved in the regulation of tumorigenesis, angiogenesis, and metastasis [ 92 ]. Additionally, a likely pathogenic variant NM_017672: c.C1337G, p.A446G (chr15: 50916466) in the TRPM7 gene was found.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of FOXL2 (downregulated upon RBPMS knockout) has been found to suppress cervical cancer cell proliferation and facilitate the apoptosis of these cells [ 69 , 70 ]; thus, it could be important to study the role of FOXL2 in ovarian cancer. Furthermore, the deregulation of other downregulated genes following RBPMS knockout, including PDGFD, TES, CARD16, and KNF521, has been linked to the progression of many cancer types [ 71 , 72 , 73 ], and the role of these genes in the ovarian cancer setting should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…TES functions as a necessary tumor suppressor of colorectal cancer progression by activating mitogen-activated protein kinase (p38-MAPK) signaling pathways [27]. TES suppressed the epithelial-mesenchymal transition in endometrial cancer [28] and breast cancer [29]. Other investigators have reported that TES binds to the EVH1 domain of Mena with its LIM3 domain [5].…”
Section: Discussionmentioning
confidence: 99%